The State of Spirituality in India and Insights for Marketing - Pillania, Rajesh K. (Indian Journal of Marketing, 2021)
There is an emerging paradigm shift in management over the last two decades towards spirituality. Before going for studies in marketing and spirituality in the Indian context, it is essential to first understand spirituality in the Indian context because India is a diverse country. However, there is lack of a pan – India study to understand the current state of spirituality. This research paper filled this research gap by studying spirituality in India's 36 states and union territories. The results showed differences across states and union territories, small states and big states, islands and mainland, and across different regions. Marketing professionals can use the findings of the study while designing the marketing strategy and marketing mix to reach out to the consumers in a better way. One limitation of this work is that it could have undertaken a pilot project or a case study to relate the findings on spirituality with the spirituality paradigm in the Indian context.